Conservative management of dentigerous cysts in children - Arjona-Amo, Manuel (J Clin Exp Dent, 2015)
PURPOSE AND INTRODUCTION: Dentigerous cysts are epithelial in origin and are the most commonly found cyst in children. The majority of these lesions are usually a radiological finding and are capable of quite large before being diagnosed. The standard treatment for these cysts is the enucleation and the extraction of the affected tooth. However, if the patient is a child and the affected tooth is not developed, a more conservative attitude should be considered. MATERIAL AND METHODS: (Clinical case): A 7-year-old patient is presented with an eruptive backlog of the lower permanent first molars. Radiological examination reveals two radiolucid lesions in relation to them, which are compatible with a dentigerous cyst, and in relation to the inferior aveolar nerve and various germs. A partial enucleation is carried out, maintaining all the dental germs related to the cyst in mouth and monitoring the patient until the case study is over. RESULTS AND DISCUSSION: Diagnosis and early treatment of these lesions in children is of great importance, especially in cases where the lesions enclose permanent teeth. CONCLUSIONS: Whenever possible, a conservative attitude should be taken, one that allows for the maintenance of the dentition and treatment of the associated cyst in order to not compromise either the occlusion or the mental state of these patients. Key words:Dentigerous cyst, conservative treatment, dental impaction, child.